Quantum yield measurements by thermal lens in highly absorbing samples: The case of highly doped rhodamine B organic/silica xerogels - Dos Santos, J. F.M.; Zanuto, V. S.; Ventura, M.; Bramorski, C. B.; Catunda, T.; Manoel, D. S. [UNESP]; Malacarne, L. C.; De Vicente, F. S. [UNESP] (American Physical Society (APS), 2019)
In this work, rhodamine B-doped GPTS/TEOS-derived organic/silica monolithic xerogels were prepared by the predoping sol-gel process. Thermal lens method was applied to determine thermo-optical properties of the samples. Since the samples present a high optical absorption coefficient, the high absorption theoretical TL model was introduced. Thermal diffusivities, optical absorption coefficients, and fluorescence quantum yield values were determined for samples with different rhodamine B (RhB) concentrations, from 10-5 to 10-2 M. The dye-doped organic/silica xerogels present a high fluorescence quantum yield (up to 90%), maintaining the value over 50% until a concentration of ∼1.6 mM. To the best of our knowledge, RhB-doped transparent monoliths with a high fluorescence quantum yield with the highest RhB concentration reported in a solid hybrid matrix were obtained.